Development of novel lithocholic acid derivatives as vitamin D receptor agonists. Issue 16 (15th August 2019) - Masuno, Hiroyuki; Kazui, Yuko; Tanatani, Aya; Fujii, Shinya; Kawachi, Emiko; Ikura, Teikichi; Ito, Nobutoshi; Yamamoto, Keiko; Kagechika, Hiroyuki
Graphical abstract: Abstract: Lithocholic acid (2 ) was identified as the second endogenous ligand of vitamin D receptor (VDR), though its binding affinity to VDR and its vitamin D activity are very weak compared to those of the active metabolite of vitamin D3, 1α, 25-dihydroxyvitamin D3 (1 ). 3-Acylated lithocholic acids were reported to be slightly more potent than lithocholic acid (2 ) as VDR agonists. Here, aiming to develop more potent lithocholic acid derivatives, we synthesized several derivatives bearing a 3-sulfonate/carbonate or 3-amino/amide substituent, and examined their differentiation-inducing activity toward human promyelocytic leukemia HL-60 cells. Introduction of a nitrogen atom at the 3-position of lithocholic acid (2 ) decreased the activity, but compound6 bearing a 3-methylsulfonate group showed more potent activity than lithocholic acid (2 ) or its acylated derivatives. The binding of6 to VDR was confirmed by competitive binding assay and X-ray crystallographic analysis of the complex of VDR ligand-binding domain (LBD) with6 .